2019
DOI: 10.1101/657205
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain Network Mechanisms of General Intelligence

Abstract: We identify novel mechanisms of general intelligence involving activation patterns of largescale brain networks. During hard, cognitively demanding tasks, the fronto-parietal network differentially activates relative to the default mode network, creating greater "separation" between the networks, while during easy tasks, network separation is reduced. In 920 adults in the Human Connectome Project dataset, we demonstrate that these network separation patterns across hard and easy task conditions are strongly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 116 publications
0
7
0
Order By: Relevance
“…For example, a recent large-scale study using the UK Biobank dataset (n=~30,000) reported that total brain volume, as well as multiple global measures of grey and white matter macro-and microstructure (especially, in older participants), explained substantial variance in fluid intelligence (Cox et al, 2019). Another large-scale study used the Human Connectome Project dataset (n=920) to show that the strength of functional dissociation between the MD network and the default mode network (DMN) (Power et al, 2011) during an n-back working memory task explains substantial variance (~25%) in IQ scores (Sripada et al, 2019), similar to the current study, although the same measure extracted from two other executive tasks (also in the HCP dataset) explained only ~10% of variance in IQ scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent large-scale study using the UK Biobank dataset (n=~30,000) reported that total brain volume, as well as multiple global measures of grey and white matter macro-and microstructure (especially, in older participants), explained substantial variance in fluid intelligence (Cox et al, 2019). Another large-scale study used the Human Connectome Project dataset (n=920) to show that the strength of functional dissociation between the MD network and the default mode network (DMN) (Power et al, 2011) during an n-back working memory task explains substantial variance (~25%) in IQ scores (Sripada et al, 2019), similar to the current study, although the same measure extracted from two other executive tasks (also in the HCP dataset) explained only ~10% of variance in IQ scores.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint (which was this version posted September 6, 2019. ; https://doi.org/10.1101/110270 doi: bioRxiv preprint belong to an extended MD network) and the default mode network (DMN) (Lipp et al, 2012;Smith et al, 2015;Sripada et al, 2019), and with the strength of synchronization among non-MD brain regions (Dubois et al, 2018;Hilger et al, 2017). These apparently discrepant results could reflect the complexity of the brainbehavior relationship in the domain of executive abilities, with perhaps multiple underlying cognitive constructs and neural mechanisms contributing.…”
Section: Introductionmentioning
confidence: 99%
“…The highly creative brain shows a fine balance between integration and segregation of control networks and DMN, while the less creative brain is dominated by motor and visual processing (Zhuang et al, 2021). Moreover, individuals with strong and flexible connectivity between executive networks and DMN score more highly on tests of intelligence (Sripada et al, 2019) and produce more creative ideas (Beaty et al, 2015; 2016; 2014; 2017; 2019). SCN regions are argued to be important for the interaction between executive and DMN regions, because they fall at the juxtaposition of DMN and MDN (Wang et al, 2020); SCN is unique in showing shared intrinsic and structural connectivity to both DMN and MDN which are often anti-correlated (Davey et al, 2016).…”
Section: Figurementioning
confidence: 99%
“…General Cognitive Ability (GCA) scores were computed by fitting a bifactor model to behavioral tasks from the NIH toolbox, the Rey Auditory Verbal Learning Task, the WISC-V, and the "Little Man" task (66). GCA factor scores were generated using expected a posteriori scoring (67).…”
Section: Criterion Variables: Neurocognitionmentioning
confidence: 99%